Sea surface skin temperature retrieval from HY-1D COCTS observations - Li, Zhuomin; Guan, Lei; Chen, Rui (Frontiers in Marine Science, 2023)
The Haiyang-1D (HY-1D) satellite is an operational satellite for observing the ocean and was launched on 11 June 2020. The Chinese Ocean Color and Temperature Scanner (COCTS) is on board the HY-1D satellite and the 11 μm and 12 μm channel data can be used for sea surface temperature (SST) retrieval. This paper uses the COCTS 11 μm and 12 μm channel brightness temperatures (BTs) for skin SST retrieval based on atmospheric radiative transfer modeling. Representative atmospheric profiles are selected from the global ERA5 atmospheric profiles, and the 11 μm and 12 μm channel BTs are simulated using MODerate resolution atmospheric TRANsmission (MODTRAN) with the selected profiles. The skin SST retrieval algorithm is determined for each latitude band based on the simulated BT and ERA5 sea surface skin temperature. Cloud detection is performed using the visible channel data, 11 μm and 12 μm channel BT, retrieved COCTS SST, and the reference SST. The retrieved COCTS skin SST is validated with the in situ SST and the Visible Infrared Imaging Radiometer Suites (VIIRS) SST. The global COCTS SST from May to July 2021 was retrieved and evaluated. The time window is 1 h, and the spatial window is 0.01°×0.01°. The bias of COCTS SST and in situ SST is -0.11°C, the standard deviation is 0.54°C, the median is -0.08°C, and the robust standard deviation is 0.47°C. The bias of COCTS SST and VIIRS SST is 0.03°C, the standard deviation is 0.53°C, the median is 0.06°C, and the robust standard deviation is 0.49°C. The results demonstrate that the algorithm performs well for the global coverage.